Supplier evaluation and selection using revised Tagichi loss function. - Sadigh, Aghdas Naimi; Zulkifli, Norzima; Hong, Tang Sai; Abdolshah, Mohammad (Asian Network for Scientific Information, 2009)
Assessing quality as one of the main criteria for supplier selection is so important. Literature review showed that in order to evaluate the quality of suppliers, some methods such as rate of rejects, quality certification, easy to repair, reliability and process capability indices are so common. These methods can assess just one aspect of an organization and are not appropriate tools for assessing the real quality of the product supplied by the supplier, while loss functions are suitable tools to evaluate the quality. To overcome this problem and because of features of revised Taguchi loss function, this study proposes the use of the revised Taguchi loss function for supplier evaluation and selection. After assessing the quality, using the expected value of the revised Taguchi loss function and integrating of this function with the cost of purchasing and transportation, a simple Linear Programming (LP) model will appear. A numerical example provides the explanation. This model is a very simple linear programming model with excellent estimation of quality, which integrates the quality of supplier, cost of purchasing and transportation costs.